(untitled) (Journal of Pathology of Nepal, 2015)
Background: Tissue diagnosis is an essential step to come to a confirmed diagnosis in oral lesions where clinical examination alone can often be difficult and inaccurate. The aim of this study was to assess the use of histopathological services by the dental department and to correlate the clinicopathological diagnosis. Materials and Methods: This is an histopathological database analysis of dental biopsies in 23 years from 1989 to 2012 in Patan Hospital. The variables studied were age, sex, clinical and histopathological diagnosis. SPSS version 16 was used as an analytical tool. Results: Out of 396 dental biopsies 203 (51.3%) were females and 193 (48.7%) were males with mean age 34.34 years and standard deviation of 17.9 years. The neoplastic and non neoplastic conditions were 44% and 56% respectively. Conclusion: Most diagnoses were benign in nature and had an inflammatory etiology.